The Relationship between Education and Culture: A Literature Review - Iqbal Nuari; Firman Firman; Riska Ahmad (Program Studi Bimbingan dan Konseling FKIP UMSU, 2021)
Education cannot be separated from human life, because education is a process of someone entering a culture and making that person behave and follow that culture. Human behavior, consciously or unconsciously, is a formation of the existing culture in the surrounding environment. The scope of the cultural scope is very broad covering all aspects of human life, so education is also one of these aspects. Education cannot be separated from culture, because education is a part of culture which is an effort to provide basic knowledge as a provision for life, basic knowledge for life provisions which is meant here is culture. Therefore, the relationship between education and culture is very close to one another, in the context of the world of education a student is educated to become an individual who is cultured according to the norms and values that exist in that culture